Selective Spectrophotometric Method for the Determination of Molybdenum in X80 Pipeline Steel - Xiaodong1, Shao; Ying2, Li; Yangqin1, Liu; Fagen1, Li (Asian Journal of Chemistry, 2011)
A highly selective and sensitive spectrophotometric method for the determination of molybdenum in high grade pipeline steel has been presented. This method was based on the chromogenic reaction between molybdenum(V) and sodium thiocyanate. Employing stannous chloride as a reductant, molybdenum(VI) was reduced to molybdenum(V) at the room temperature. The obtained molybdenum(V) formed an orange-red-coloured (1:5) ligand complex with thiocyanate. The absorbance of the complex was measured at 470 nm and the molar extinction coefficient (e) is 1.75 × 104 L mol-1 cm-1. Under the optimum reaction conditions the absorption value was proportional to the concentration of molybdenum in the range of 0.11-0.89 % (w/w) and the relative standard deviation was less than 3.0 %. The proposed method was free from the interference from a large number of analytical important elements and has been applied satisfactorily to the determination of molybdenum in X80 pipeline steel and X70 pipeline steel samples with the improved accuracy and precision.